High-speed train overturning safety under varying wind speed conditions. Issue 198 (March 2020) - Liu, Dongrun; Wang, Tiantian; Liang, Xifeng; Meng, Shi; Zhong, Mu; Lu, Zhaijun
Abstract: Given that the operation speeds of high-speed trains are rising constantly and considering the lightweight body technology that is being applied widely, vehicle systems have become much more sensitive to external excitation. When a train passes through a wind zone railway, for example, it often encounters an abrupt wind speed change phenomenon caused by the surrounding wind being affected by the local terrain. Such a phenomenon makes it more difficult to ensure train safety and commuter comfort. However, few studies have focused on the effect of changing wind speeds on a train's operational safety. In this study, we developed a crosswind model on the basis of measured wind speed curves and investigated the effects of a single wind speed change and continuous wind speed changes on train dynamics. In addition, we also considered the influence of the rate of wind speed changes, the duration of the maximum wind speed, and changes in wind speed with different amplitudes. By considering the most critical wind speed changing conditions and by setting the overturning coefficient as the safety limit, we obtained the critical overturning wind speed under changing wind speed conditions. As a consequence, we suggested the process for estimating a wind speed interval for safe train operation under abruptly changing wind speed conditions. Highlights: Car-body vibration characteristics under strong wind conditions is investigated by full-scale test. The effect of wind speed abrupt change phenomenon on the high-speed train overturning safety. The process for estimating a wind speed interval for safe train operation under abruptly changing wind speed conditions.